Winter Olympics 2022 in Beijing: A Must-be Success Story. Issue 2 (2nd April 2020) - Xin, Yi; Kunzmann, Klaus R.
Abstract: In 2022, Beijing will host the Winter Olympic Games. For the first time, a city has been selected by the Olympic Committee to host summer as well as the Winter Olympics. While people in more and more countries around the world are voting against the candidature for the Olympic Games, the aim of the Chinese Government is to demonstrate to the world and to its people that the capital city has the capacity to host and benefit from a global event. Using the example of the Winter Olympic Games in Beijing, this paper aims to show how the Olympic Games have evolved from a peace project in 1896 to a media-dominated commercial venue in the 21st century. The paper will show how a country that has no winter sports tradition is using the event to promote winter sports industries and demonstrate how a city with no local winter sports facilities is preparing for such an event, and how it is using the event to demonstrate national pride, and as a catalyst for urban regeneration and regionalisation.